Oprawy woluminów z księgozbioru kanonika gnieźnieńskiego Leonarda Walkonowskiego w zasobach Archiwum Archidiecezjalnego w Gnieźnie - Franczak, Radosław (Archiwa, Biblioteki i Muzea Kościelne, 2017)
The article presents additional volumes found in the collections of the former Cathedral Library, formerly owned by the Canon of Gniezno Leonard Walkonowski, (around 1550-1617). The author pays special attention to the bindings of the volumes, trying to determine when and where they were made. On the other hand, thanks to a thorough analysis of the supralibros, it was possible to determine Walkonowski’s affiliation with the Poraj family.